RANCANG BANGUN SISTEM INFORMASI INVENTARIS BERBASIS MULTIMEDIA AKSES ONLINE - Sriadhi Sy (Jurnal Sistem Informasi, 2016)
AbstractInventory management manually inhibit the performance of institutions.This research was aimed at developing a multimedia-based inventory information system program that can meet users’ specific needs. The information system program was developed on multimedia basis to produce output of inventory data in the form of 3D texts and visuals that are accessible online to multi users. The development research adopted the SLDC method. Initially, the program was developed using XAMPP as the local web server that includes Apache Web Server, PHP Script Language, MySQL Database, and phpMyAdmin Database Manager.Data were collected through observation, interviews and document study of educational institutions and public institutions. The program’s feasibility was tested by Stub Testing, Unit Testing, Black Box Testing, and White Box Testing, as well as Integration Testing. Its execution includes access modules with system login as the main access gate. The program database scheme includes (1) System Login, (2) Menu Manager,(3) Data Entry, (4) Circulation or Transaction, (5) Maintenance, and (6) Report. The information system model is capable of presenting information in the form of texts or images, and the data input uses the barcode system.The system provides access to a menu of top-down and bottom-up to facilitate the use and meet the specific needs and complete. The system was designed as an open source program, so it is open to development for studio or workshopand library information system. Key Words: inventory, information system, multimediaAbstrakPengelolaan inventaris secara manual menghambat kinerja institusi. Penelitian ini bertujuan membangun program sistem informasi inventaris berbasis multimedia yang dapat mengakomodir kebutuhan spesifik dari pengguna. Program sistem informasi dibangun berbasis multimedia sehingga menghasilkan output berupa data inventaris dalam bentuk teks maupun visual 3D, dan dapat diakses multi user dalam jaringan. Penelitian pengembangan ini menggunakan metode SLDC. Pada awalnya program dibangun menggunakan XAMPP sebagai web server lokal yang mencakup Apache Web Server, PHP Script Language, MySQL Database, dan phpMyAdmin Database Manager.Pengambilan data dilakukan melalui observasi, wawancara dan studi dokumen dari institusi pendidikan dan institusi umum. Kelayakan program diuji dengan Stub Testing, Unit Testing, Black Box Testing dan White Box Testing, serta Integration Testing. Eksekusi program memiliki modul akses dengan sistem login sebagai gerbang akses utama. Skema database program meliputi (1) Sistem Login, (2) Menu Manajer,(3) Pendataanalat, (4) Sirkulasiatautransaksi, (5) Pemeliharaan, (6) Laporan. Model sistem informasi ini mampu menyajikan informasi dalam bentuk teks, tabel dan gambar 3D, serta input data dapat menggunakan sistem barcode. Sistem menyediakan menu akses secara top-down dan bottom-up untuk memudahkan penggunaaan dan memenuhi kebutuhan spesifik dan lengkap. Sistem ini didisain sebagai open source program sehingga terbuka dikembangkan untuk sistem informasi studio atau bengkel serta perpustakaan. Kata Kunci : inventaris, sistem informasi, multimedia